Implementing a Psychiatric Behaviours of Concern emergency team in an acute inpatient psychiatry unit: Staff perspectives. (3rd April 2020) - Digby, Robin; Bushell, Hannah; Bucknall, Tracey K.
Abstract: Behaviours of concern including aggression are widespread in mental health inpatient settings. Restrictive interventions such as restraint and seclusion can cause additional trauma to already traumatized patients. To decrease use of these interventions in an acute psychiatric unit in Melbourne, Australia, a Psychiatric Behaviours of Concern (Psy‐BOC) response team was introduced. In a Psy‐BOC call, senior medical, nursing, and allied health staff respond to escalating behavioural situations to work with the primary treating team to implement clinical interventions of least restrictive practice. Here, we present qualitative findings reporting staff response to Psy‐BOC. The study complied with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Twenty‐four staff participated in five focus groups. Four themes were identified: Identifying behavioural deterioration, responding to behaviours of concern, staff reactions, and barriers. Although staff were skilled in recognizing and de‐escalating behaviours of concern, patients were secluded when heightened risk was perceived. The adoption of Psy‐BOC was met with some resistance to the cultural change required to adopt this new model. Increased awareness, early identification of behaviours of concern, and pressure from management resulted in reductions in restrictive interventions. Management of patients with drug‐induced psychosis without restraint presented specific difficulties. The ward setting was challenging, offering no break‐out spaces for patients, and few comfortable areas. Some staff appreciated the advice and expertise of the Psy‐Boc team, others felt disempowered and undermined. Improving leadership, staff education, support and collaboration, and including frontline staff in refining the process could enhance the Psy‐BOC response and increase safety for all.